Anemia, Blood Transfusion, and Filter Life Span in Critically Ill Patients Requiring Continuous Renal Replacement Therapy for Acute Kidney Injury: A Case-Control Study - Hasan M. Al-Dorzi; Nora Ali Alhumaid; Nouf Hamad Alwelyee; Nouf Mubark Albakheet; Ramah Ibrahim Nazer; Sadal Khalid Aldakhil; Shahad Abdulaziz AlSaif; Nazish Masud (Critical Care Research and Practice)
Background. Filter clotting is frequent during continuous renal replacement therapy (CRRT), which increases anemia risk. We studied anemia and blood transfusion in critically ill patients requiring CRRT for acute kidney injury and assessed the relationship between CRRT filter life span and PRBC transfusion. Methods. A case-control study was conducted at a tertiary-care intensive care unit (ICU) where CRRT cases were matched with controls for age, gender, admission category, and severity of illness. Daily hemoglobin levels, blood transfusions, and life span of CRRT filter were noted. CCRT patients were categorized according to the median of the filter life span (20 hours). Results. Ninety-five cases and 102 controls were enrolled. The hemoglobin level on admission was similar in the two groups, yet cases had significantly lower hemoglobin levels than controls (72.8 ± 15.3 versus 82.5 ± 20.7 g/L, p<0.001) during ICU stay. Anemia <70 g/L occurred in 50% of cases and 19% of controls (p<0.001). Most (56.3%) cases were transfused compared with 29.9% for controls (p<0.001) with higher number of transfused packed red blood cell (PRBC) units in cases (2.6 ± 4.0 versus 1.5 ± 3.2 units per patient, p=0.03). Patients with shorter versus longer filter life had similar hemoglobin level in the first 7 days of CRRT with no difference in PRBC transfusion requirement. Prefilter heparin use and hemodialysis access location were not associated with longer filter life span. The mortality was similar in patients with shorter versus longer filter life. Conclusions. CRRT in ICU was associated with larger drop in hemoglobin and more PRBC transfusion. Shorter (<20 hours) versus longer CCRT filter life was not associated with increased PRBC transfusion.